REAL TIME ANALYSIS AND FORECASTING OF STRATA CAVING BEHAVIOUR DURING LONGWALL OPERATIONS - Tadisetty S.; Matsui K.; Shimada H.; Gupta R.N. (My University, 2006)
Discontinuous manual observations and irregular caving characteristics of roof rocks often lead to improper decisions resulting in accidents and production loss. Hence, systematic monitoring of the hanging roof behind the chock shields is necessary for safe and productive mining operations. A real-time application was successfully implemented in an Indian mine for forecasting of hanging roof behaviour to enhance safety and productivity. This paper reports the functioning of real-time TWAP (time weighted average pressure) analysis in the forecasting of hanging roof behaviour in real time.
Keywords: REAL-TIME SYSTEM; STRATA CAVING; CONTINUOUS MONITORING; TIME-WEIGHTED AVERAGE PRESSURE ANALYSIS; WIRELESS TRANSMISSIONS; TUNNELING